Individual Baseline Balance Assessments in a Large Sample of Incoming NCAA Division I Athletes Using a Force Plate System - Scott A. Weismiller; Robert Monaco; Jason Womack; Brandon Alderman; Carrie Esopenko; Fiona N. Conway; Kyle Brostrand; Allison Brown; Nicola L. de Souza; Jennifer F. Buckman (North American Sports Medicine Institute, 2021)
# BACKGROUND Individualized baseline testing is resource and time intensive. The use of normative data to approximate changes after a suspected concussion is thus an appealing alternative. Yet, few peer-reviewed, large-sample studies are available from which to develop accurate normative averages of balance using force-plate technology. # PURPOSE This study sought to validate a normative dataset from the force-plate manufacturer and examine the magnitude and nature of sample variability. # STUDY DESIGN Cross-sectional. # METHODS Baseline balance and self-reported sex, sport, and concussion history were assessed in 533 prospective collegiate athletes (45% female) during pre-participation physical examinations. Balance was measured using four stances from the modified Clinical Test of Sensory Interaction and Balance and quantified as Sway Index Scores with the Biodex Biosway Portable Balance System. Group averages are contrasted to data from the force-plate manufacturer. Individual variability around these averages was visualized and analyzed by sex and sport. # RESULTS Male student athletes showed significantly more sway in the eyes open, soft stance condition than female athletes. These differences were maintained when concussion history was included as a covariate. Athletes, particularly male athletes, in the high versus low contact sport group showed significantly more sway in the eyes open, soft surface and the eyes closed, hard and soft surface stances. # CONCLUSION There was substantial individual variability that was partially explained by sex differences and sport differences. The development of normative averages for sway may benefit from consideration of sex and sport. Further studies should characterize other factors that influence baseline balance in collegiate athletes. # LEVEL OF EVIDENCE 2b